The Impact of Augmented Reality (AR) Applications in English Language Learning for Children with Autism: A Systematic Literature Review - Lenny Solo; Ifan Iskandar; Ratna Dewanti (Universitas Islam Negeri Palopo, 2025)
This study aims to explore the use of Augmented Reality (AR) in English language learning for children with autism spectrum disorder (ASD) through a systematic literature review. The main objective of this research is to assess how AR can enhance the English language skills of children with ASD, evaluate its effectiveness in increasing student motivation and engagement in learning, and identify the challenges encountered in its implementation. The population studied consists of research that discusses the use of AR in educational contexts for children with ASD, while the research sample includes articles published within the last five years that are relevant to this topic. The methodology employed is a systematic literature review, with data collected through a search of relevant articles from various academic databases, including Google Scholar, PubMed, ScienceDirect, and JSTOR. The collected data were then analyzed using a thematic analysis approach to identify emerging patterns related to the use of AR in English language learning, its benefits, the challenges encountered, and its impact on language skills and social interaction in children with ASD. The findings reveal that AR applications have significant potential to improve the English language skills of children with ASD, particularly in speaking, listening, and vocabulary. Furthermore, AR is also effective in increasing student motivation and engagement by providing an enjoyable and interactive learning experience. However, the challenges identified include hardware limitations, children's difficulty in adapting to new technologies, and the need for teacher training to maximize the effectiveness of AR use. Therefore, the successful implementation of AR in education for children with ASD heavily depends on infrastructure readiness and appropriate training.